Validating the Efficacy of Two Burr-Hole Craniostomy over Mini-Craniotomy for Chronic Subdural Hematoma Drainage - Hegde, Pranoy; Nayak, Bharat; Madishetty, Aditya; Perikal, Parichay J.; Furtado, Sunil V. (Asian Journal of Neurosurgery, 2023)
Background There is an increasing incidence of chronic subdural hematoma due to extended life expectancy and associated trauma and fall risk. This retrospective study evaluates the efficacy of two burr-hole craniotomy over mini-craniotomy.Methods Sixty-five patients were recruited over 2 years, of which 56 were male and 9 were females. A patient with a chronic subdural hematoma either underwent burr-hole craniostomy or mini-craniotomy for hematoma evacuation. Glasgow coma scale (GCS) and modified Rankin score were used to assess the neurological status and interventional outcome at discharge and follow-up, respectively. A head CT scan was performed at 3 week and 3 month follow-up.Statistical Analysis Categorical data are presented as frequency and percentage, while non-categorical data are represented as mean ± SD. Statistical significance for difference in outcome between the two groups was analyzed using the chi-square test and p-value less than 0.05 was considered statistically significant.Results The mean age of patients was 55.6 years. Headache (35 cases), hemiparesis, and altered sensorium were seen in 20 patients, each with the main presenting symptoms. Trauma history was noted in 69.2% of patients. One (3.7%) hematoma recurrence in the burr-hole group and four (8.3%) in the mini-craniotomy group was recorded. The mean operative time was longer in the minicraniotomy group (124.2 min vs. 75.4 min; p < 0.001). A higher incidence of recurrence was noted in the craniotomy group (8.3%) than the burr-hole group (3.7%). No statistical difference in the recurrence rate, duration of hospital stay, GCS at discharge, modified Rankin score between the two study groups at discharge was noted.Conclusion Two burr-hole craniostomy is a safe and effective surgical option to treat chronic subdural hematoma. It is also validated in patients on anticoagulants and antiplatelet medications with adequate pre-surgical correction of coagulation parameters.
Keywords: burr-hole; chronic subdural hematoma; craniotomy; membrane; recurrence